1994
DOI: 10.1111/j.1432-1033.1994.tb18958.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of the complex of dystrophin and its associated proteins into several unique groups by n‐octyl β‐d‐glucoside

Abstract: Dystrophin is purified as a complex with several proteins from the digitonin-solubilized muscle cell membrane. Most of dystrophin-associated proteins (DAPs) are assumed to form a large oligomeric transmembranous glycoprotein complex on the sarcolemma and link dystrophin with a basement membrane protein, laminin. In the present study, we found that the purified dystrophin-DAP complex was dissociated into several groups by n-octyl-P-~-glucoside treatment. In particular, we found that the glycoprotein complex sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
167
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 35 publications
18
167
0
1
Order By: Relevance
“…It also appears that the absence of 7-sarcoglycan leads to a reduction of cx-and [~-sarcoglycan suggesting a close association between these three proteins in muscle sarcolemma. The close association of these sarcoglycan proteins has previously been suggested by Yoshida et al [36]. They have shown that n-octyl-13-D-glucoside disrupts the DGC into four groups of proteins: (i) ~-and [3-dystroglycan; (ii) dystrophin; (iii) the syntrophins; and (iv) c~-, 13-and y-sarcoglycan.…”
Section: Resultssupporting
confidence: 53%
“…It also appears that the absence of 7-sarcoglycan leads to a reduction of cx-and [~-sarcoglycan suggesting a close association between these three proteins in muscle sarcolemma. The close association of these sarcoglycan proteins has previously been suggested by Yoshida et al [36]. They have shown that n-octyl-13-D-glucoside disrupts the DGC into four groups of proteins: (i) ~-and [3-dystroglycan; (ii) dystrophin; (iii) the syntrophins; and (iv) c~-, 13-and y-sarcoglycan.…”
Section: Resultssupporting
confidence: 53%
“…[1][2][3][4][5][6][7][8] Mutations in four genes encoding sarcoglycan proteins (␣-, ␤-, ␥-and ␦-SG) are responsible for various forms of autosomal recessive limb-girdle muscular dystrophy (LGMD 2D, 2E, 2C and 2F, respectively). [9][10][11][12][13][14][15][16] This heterogeneous group of diseases nevertheless shares a common feature in that a primary deficiency of any of the sarcoglycan proteins leads to the reduction or the absence of all other members of the SG-SSPN complex.…”
Section: Introductionmentioning
confidence: 99%
“…The 43DAG is the same as A3a, as determined by peptide sequence analysis of the purified gel band. A3b is distinct from A3a, as it has a different proteolytic cleavage pattern (14) and is unable to bind dystrophin (16). The 56-kDa amino-terminal core protein once glycosylated at many of the potential O-glycosylation sites gives rise to the fully processed 156DAG (15).…”
Section: Dystrphin and Utrophin Genesmentioning
confidence: 99%